2018
DOI: 10.1186/s12889-018-5885-8
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships in adolescence and heavy episodic drinking from youth to midlife in Finland and Sweden — examining the role of individual, contextual and temporal factors

Abstract: BackgroundApplying the Process-Person-Context-Time (PPCT) model of the bioecological theory, this study considers whether proximal processes between the individual and the microsystem (social relationships within family, peer group and school) during adolescence are associated with heavy episodic drinking (HED), from youth to midlife, and whether the macro level context (country) plays a role in these associations.MethodsParticipants of two prospective cohort studies from Finland and Sweden, recruited in 1983/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In general, women reported more symptoms of internalized disorders such as anxiety, depression and somatic symptoms [34,59,60] while alcohol misuse was higher among men [42,61]. Measuring the symptoms of ill mental health at the age of 16, 21, 30 and 43 indicated that depressive, anxiety and somatic symptoms co-exist from the adolescence till midlife among the participants and the level of symptoms at each point was strongly associated with previous and future level of the symptoms [60].…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In general, women reported more symptoms of internalized disorders such as anxiety, depression and somatic symptoms [34,59,60] while alcohol misuse was higher among men [42,61]. Measuring the symptoms of ill mental health at the age of 16, 21, 30 and 43 indicated that depressive, anxiety and somatic symptoms co-exist from the adolescence till midlife among the participants and the level of symptoms at each point was strongly associated with previous and future level of the symptoms [60].…”
Section: Resultsmentioning
confidence: 94%
“…Poor relationship with peers at the age of 16 was associated with several indicators of ill mental health such as depressive symptoms, IMHS and FSS at the age of 43 [41,43]. Among women, poor relationship with classmates at 16 were associated with increased likelihood of heavy episodic drinking at age 30 [42].…”
Section: Micro-levelmentioning
confidence: 98%
See 2 more Smart Citations
“…Human development is impacted by an individual's interactions within all five systems (Bronfenbrenner, 1977): (a) the microsystem includes interactions with the immediate surroundings; (b) the mesosystem comprises connections and processes that take place between microsystems; (c) the exosystem involves systems of interaction where the person in development does not directly function; (d) the macrosystem is formed by overarching cultural patterns and subcultures that influence broader systems; and (e) the chronosystem incorporates how the individual is impacted over time. In Bronfenbrenner's PPCT model (1995, 2005, the process refers to dynamic interaction between the individual and their environment, the second concept of person refers to an individual's characteristics, the third concept of context describes the environmental systems around the person, and the fourth concept of time indicates temporal aspects (Berg et al, 2018). The PCCT framework can be especially useful in understanding the experiences of immigrants and refugees who are moving through multiple cultures and systems to get to their preferred destination.…”
Section: Bronfenbrenner Ecological Systems Theorymentioning
confidence: 99%